ELEMENTARY SCHOOL TEACHERS ABILITY IN WRITING INDONESIAN LANGUAGE SENTENCES STRUCTURE (Kemampuan Guru Sekolah Dasar dalam Menulis Struktur Kalimat Bahasa Indonesia) - Apri Damai Sagita Krissandi (Kantor Bahasa Sulawesi Tenggara, 2020)
This research aims to describe the Mahakam Ulu District elementary school teachers ability in writing sentence structure of Indonesian language. This research is adescriptive qualitative research. The subject of this study consisted of 20 elementary school teachers in Mahakan Ulu District. The data were collected by surveys. The instrument was in the form of an instruction to make three sentences with structure of: 1) S-P-O; 2) S-P-O-K; 3) K-S-P-O. The data validity was obtained trough triangulation. The results show that the writing ability of teachers in Mahakam Ulu, East Kalimantan is still lacking. This can be seen from the conformity of the sentences produced with the instructions given. The sentences that correspond to the instructions are 36.7%, while the percentage of sentences that do not correspond to the instructions is 63.3%. The instruction is to make sentences with S-P-O, S-P-O-K, and K-S-P-O patterns. Sentences correspond to the S-P-O pattern are 55%, while the percentage of sentences that do not correspond to the S-P-O pattern is 45%. The sentences correspond to the S-P-O-K pattern are 30%, while the sentences that do not correspond to the S-P-O-K pattern are 70%. The sentences correspond to the K-S-P-O pattern are 25%, while the sentences that do not correspond to theK-S-P-O pattern are 75%. Errors made by teachers are: 1) errors in objectfunction; 2) errors in adverbfunction; 3) errors in complementfunction; and 4) errors in punctuations, prepositions, and dictions.Penelitian ini bertujuan mendeskripsikan kemampuan menulis guru SD Kabupaten Mahakam Ulu dalam menulis struktur kalimat bahasa Indonesia. Penelitian ini merupakan penelitian kualitiatif deskriptif. Strategi pengumpulan data menggunakan survei. Subjek penelitian ini terdiri atas 20 orang guru SD Kabupaten Mahakan Ulu. Instrumen penelitian berupa soal. Instrumen soal berupa perintah membuat tiga kalimat dengan struktur: (1) S-P-O; (2) S-P-O-K; (3) K-S-P-O. Keabsahan data diperoleh dengan menggunakan triangulasi. Hasil penelitian menunjukkan bahwa kemampuan menulis guru-guru Mahakam Ulu, Kalimantan Timur masih tergolong kurang. Hal ini dapat dilihat dari kesesuaian kalimat-kalimat yang diproduksi dengan instruksi yang diminta. Kalimat yang sesuai instruksi sebanyak 36,7%, sedangkan persentase kalimat yang tidak sesuai dengan instruksiberjumlah 63,3%. Persentase kesesuaian kalimat dengan pola (1) adalah 55%, sedangkan kalimat yang tidak sesuai dengan pola sebanyak 45%; persentase kesesuaian kalimat yang sesuai dengan pola (2) adalah 30%, sedangkan yang tidak sesuai adalah 70%; persentase kesesuaian kalimat yang sesuai dengan pola (3) berjumlah 25%, sedangkan yang tidak sesuai berjumlah 75%. Kesalahan yang dilakukan para guru meliputi kesalahan fungsi objek, kesalahan fungsi keterangan, kesalahan fungsi pelengkap, dan 4) kesalahan tanda baca, kata depan, dan diksi.